Teachers' Direct and Indirect Feedback Influence to Students' Speaking Performance: Students' Perceptions - Adhana, Muhammad Raihan; Farihah, Syarifah; Sari, Novita; Sy Ola, Bea Fitriyani; Eviyuliwati , Ismalianing (Jurnal Basicedu, 2023)
Teachers' feedback is useful information for student's improvement. However, students have their own way to perceive teacher feedback during speaking class. The aim of this study was to investigate students' perception towards the influence of corrective feedback from the teacher to the students during speaking class. This study applied a qualitative method by using interviews to collect the data. This study involved ten students of the English Language Education Department, Syarif Hidayatullah State Islamic University (UIN -Syarif Hidayatullah ) Jakarta. The result showed that all participants expressed a positive perspective towards direct Feedback, and perceiving it to be beneficial for learning English. Among the kinds of feedback given by the teachers, most of the participants preferred direct feedback and only one participant preferred both direct and indirect feedback. Most participants preferred direct feedback because their mistakes could be immediately corrected by the teacher, then they will try to do better in the next speaking performance. It can be concluded that direct feedback Gave positive results to the students' speaking performances. This study would assist both teachers and students by highlighting the importance of providing and accepting direct feedback.